Self-care Behaviors and Complications of Diabetes Mellitus Patients in Kamphaeng Phet Province - จารุวัฒน์ ลออศรี (Disease Control Journal, 2009)
The objectives of this survey research was to delineate knowledge on Diabetes Mellitus (DM) including selfcare behaviors, the factors influencing to self-care behaviors, ability to control blood sugar and complications from DM in Kamphaeng Phet. Four hundred of DM patients with the age of equal or more than 15 years were sampled by systematic random sampling from DM patients who attended at Out Patients Department (OPD) of government hospitals in Kamphaeng Phet. Data collecting was carried out by using questionnaires, blood sugar and complication records during June - August 2009. Data was analyzed by descriptive statistics and multiple regression model. The results revealed that the majority (86.2 and 88.4 percent) of female and male patients knew DM well. About 50.7 and 54.5 percent of male and female patients had self-care behaviors at moderate level and 48.6 and 49.2 percent of them had their behaviors at good level while only 0.7 and 2.6 percent of them had their behaviors at low level. The factors which had positive influencing to self-care behaviors at statistically significant (P-value <0.05), in female were knowledge on DM and social supporting while in male were knowledge on DM and their age. For ability to control blood sugar, 29.5 and 25.9 percent of female and male patients were unable to control blood sugar. Regarding the complication, half of female and male patients had complications from DM.